How sesquiterpenes modulate signaling cascades in cancers - Jabeen, S; Qureshi, M Z; Attar, R; Aslam, A; Kanwal, S; Khalid, S; Qureshi, J M; Aras Perk, A; Farooqi, A A; Ismail, M (Cellular and Molecular Biology, 2016)
Data obtained from high-throughput technologies has started to shed light on the interplay between signal transduction cascades and chromatin modifications thus adding another layer of complexity to the already complex regulation of the protein network. Based on the insights gleaned from almost a decade of research, it has now been convincingly revealed that sesquiterpenes effectively modulated different intracellular signaling cascades in different cancers. In this review we summarize how sesquiterpenes mediated Wnt, Shh, Notch and TRAIL induced signaling cascades.